Impact of illness and death: comparison of Load and QALY models - Tim Benson (BMJ Open Quality)
Background When allocating resources health decision-makers make trade-offs between different outcomes, such as morbidity and mortality. The Load and QALY (quality-adjusted life year) models are two approaches that have been developed to help value health and care outcomes.Methods I briefly describe preference judgements, the Load and QALY models.Results The same preference judgement, based on the standard gamble, is applied to a single hypothetical individual’s lifetime, who dies at age 75 after 3 years of illness. In this example, the morbidity/mortality ratio using the Load model is 50 times higher than using the QALY model.Conclusions These findings, placing greater value on illness, call for further exploration, and in particular, whether the Load model can reshape healthcare policies and resource allocation.